2012
DOI: 10.1029/2011jc006966
|View full text |Cite
|
Sign up to set email alerts
|

Tide‐induced vertical mixing in the Laptev Sea coastal polynya

Abstract: [1] Enhanced semidiurnal-band velocity shear across the shelf halocline layer (SHL) was found during land-fast ice edge mooring-based acoustic Doppler current profiler (ADCP) and conductivity-temperature-depth (CTD) observations over the eastern Laptev Sea shelf ($74 N, 128 E) in April-May 2008 and April 2009. In 2008, the major axis amplitude for the lunar semidiurnal M 2 tidal ellipses demonstrated intermediate maximum in the SHL at 11-13 m (15 AE 3 cm/s), gradually decreasing to subice and near-bottom layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…The result is in agreement with observational data on the Laptev Sea Shelf (Dmitrenko et al, 2008b(Dmitrenko et al, , 2012. The number of simulated periods was dictated by the time of complete system equilibration.…”
Section: Energy Balancesupporting
confidence: 79%
See 1 more Smart Citation
“…The result is in agreement with observational data on the Laptev Sea Shelf (Dmitrenko et al, 2008b(Dmitrenko et al, , 2012. The number of simulated periods was dictated by the time of complete system equilibration.…”
Section: Energy Balancesupporting
confidence: 79%
“…Whereas the Russian Arctic coast zones, and the Laptev Sea in particular, are getting more and more in the spotlight, the still insufficient amount of observational data as well as the lack of modeling efforts with fine resolution over the shelf leaves many challenges. However, certain observational evidence has already been accumulated, leading to valuable insights in tidal dynamics (Dmitrenko et al, 2012; Janout and Lenn, 2013; Lenn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the Laptev Sea shelf where strong salinity stratification is maintained by the river runoff from the Lena River, the second largest river flowing into the Arctic Ocean (e.g., Dmitrenko et al, 2010). Dmitrenko et al (2012) showed that significant velocity shear over the Laptev Sea shelf, attributed to the lunar semidiurnal baroclinic internal tide M2 with velocity ∼ 15 cm s −1 at 11 m and ∼ 7 cm s −1 at 19 m depth is required to transform the vertically stratified water into a locally mixed layer. In contrast, over the Wandel Sea shelf velocities hardly exceed 3-5 cm s −1 , and the most energetic M2 tidal currents are weak, decreasing from ∼ 2 cm s −1 beneath the ice to ∼ 1 cm s −1 below 60 m depth (Kirillov et al, 2017).…”
Section: Tracing the Origin Of The Wandel Sea Halostad Halocline Andmentioning
confidence: 90%
“…In Section 3.2 we indicated that the observed water dynamics infer the shear across the density interface separating eastward surface flow and nearbottom westward current. Another source of shear instability at intermediate depths is connected to the baroclinic mode of internal tidal motions in the area under study (Dmitrenko et al, 2005(Dmitrenko et al, , 2012. The shear-driven instability of both, the mean flow and tidal oscillations can result in entrainment at density interface depending upon the local Richardson number.…”
Section: Shear-driven and Other Mechanical Mixingmentioning
confidence: 99%